Engaging with readers: Students’ metalinguistic understanding of the use of pronouns in building reader-writer relationships - Debra Myhill (12042048) (2023)
Students’ metalinguistic understanding of the written academic argument is important both to increase writer independence and inform writing instruction. This article draws on a study which investigated undergraduate students’ metalinguistic understanding of the metadiscourse features in their own written arguments. The specific focus of the paper is to determine what metalinguistic understanding students express about the use of pronouns in written argument as engagement or stance markers to build a relationship with the reader. The analysis indicates many students believed the use of reader pronouns were inappropriate in written argument, often because this was what they had been taught. Students’ metalinguistic understanding was shaped more by notions of formality and objectivity than by understanding of how pronouns play a role in reader engagement. The article argues that greater emphasis on the function of pronouns rather than the form, drawing on metadiscourse theory, and on generating metalinguistic understanding of the differing ways that pronouns function in written argument might better support writers in agentic linguistic decision-making. Other Information Published in: Linguistics and Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.linged.2023.101184